Increasing Pesticide Use and Knowledge of the Health Effects of Endocrine Disrupting Chemicals in the Environment: A Study of Three Communities in Ghana - Benjamin Ason; David Kofi Essumang (The Journal of Population and Sustainability, 2022)
Population growth and urbanisation are contributing to the growth of the use of pesticides in Africa. However, poor understanding of the health and environmental effects of these chemicals represents a significant risk to both human health and ecosystems. Knowledge of health effects of pesticide use and endocrine disrupting chemicals (EDCs) was assessed using 300 respondents in three communities of Ghana. The data were fitted to bivariate and multivariate ordinary least squares regression models. About 76 per cent of the respondents used pesticides while 82 per cent had no knowledge of human diseases associated with pesticide use and EDCs. At the bivariate level, individuals who used pesticides had less knowledge of health effects of EDCs and pesticide use compared to their counterparts who did not use pesticides. Urban residents had more knowledge compared to rural dwellers and this robust relationship persisted at the multivariate level. Females of all ages had more knowledge of pesticides and EDCs’ effects than their male conterparts. Formal and informal education is required to improve knowledge on appropriate chemical use.